New loculoascomycete species for Ukraine, Phaeosphaeria typharum (Desm.) L. Holm (Phaeosphaeriaceae) (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The anatomical and morphological features, consortial connections, and distribution of the new species for Ukraine mycobiota, Phaeosphaeria typharum (Desm.) L. Holm are studied. Species was found in last year's leaves of Typha latifolia L. It was established that the anatomical and morphological parameters for Ph. typharum are close to those of Phaeosphaeria eustoma (Fuckel) L. Holm. A number of differences between the species were identified. Analysis of the distribution of Ph. typharum showed that the species has a wide area of distribution and forms consortial connections with 31 species of herbaceous plants of 14 genera of 7 families, saprotrophicaly developing on dead leaves and stems. Most often Ph.typharum were associated with members of families Typhaceae and Poaceae. Environmental features of the species relating to the stages of ontogeny, of habitat, and its distribution, were discussed.
Keywords: loculoascomycetes, Phaeosphaeria, new records.